2000
DOI: 10.1093/ps/79.3.363
|View full text |Cite
|
Sign up to set email alerts
|

Model of physiological stress in chickens 1. Response parameters

Abstract: A model was developed to study stress in chickens. Continuous administration of adrenocorticotropic hormone was employed (ACTH) using physiological mini-osmotic pumps. A validation of controls for this procedure showed that nonhandled (NHCON), sham surgical procedure for pump implantation (SMCON) and surgical implantation of a pump delivering saline (SALCON) were all acceptable controls. Continuous delivery of ACTH at 8 IU/kg BW/d for 7 d caused increases in plasma corticosterone (CS), glucose (GLU), cholester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
129
0
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 252 publications
(155 citation statements)
references
References 37 publications
16
129
0
10
Order By: Relevance
“…Results of the present study showed that breeder age had no effect on organ weights measured, which is in agreement with Maiorka et al (2004) (Table 3). Previous studies showed an increase in liver weight (Malheiros et al 2003;Lin et al 2006) and decrease in spleen, bursa of fabricius, and heart weights under stressful conditions (Puvadolpirod and Thaxton 2000;Lin et al 2006). There was no lighting regimen effect on relative weights of heart, liver, and bursa of fabricius.…”
Section: Resultsmentioning
confidence: 91%
“…Results of the present study showed that breeder age had no effect on organ weights measured, which is in agreement with Maiorka et al (2004) (Table 3). Previous studies showed an increase in liver weight (Malheiros et al 2003;Lin et al 2006) and decrease in spleen, bursa of fabricius, and heart weights under stressful conditions (Puvadolpirod and Thaxton 2000;Lin et al 2006). There was no lighting regimen effect on relative weights of heart, liver, and bursa of fabricius.…”
Section: Resultsmentioning
confidence: 91%
“…Os resultados corroboram os encontrados por Puvadolpirod & Thaxton (2000), que, injetando o hormônio ACTH em aves, em uma simulação do que acontece no EPC, não encontraram diferenças na quantidade de células vermelhas. No caso deste experimento, o estresse cíclico por calor pode ter sido ameno a ponto de não causar desidratação, nem alterações no eritrograma dos frangos.…”
Section: Resultsunclassified
“…Este achado corrobora os obtidos por Revidatti et al (2002), que não encontraram diferenças para glicose de frangos submetidos a estresse por manejo. Segundo Puvadolpirod & Thaxton (2000), que encontraram maiores valores de glicose em frangos injetados com hormônio ACTH, a hiperglicemia relaciona-se com quadros de estresses agudos nos quais o fator de estresse atua de forma súbita. As respostas observadas neste experimento indicam possível aclimatação das aves sob EPC (González & Silva (2003).…”
Section: Médias Seguidas Por Letras Diferentes Na Coluna Diferem (Meaunclassified
“…It is known that stress conditions affect the H/L ratio and leukocyte count (Gross & Siegel 1983;Puvadolpirod & Thaxton 2000). Under stress conditions, the number of lymphocyte, eosinophil, monocyte and haematocrit values shows a decline, whereas the number of basophil and heterophil increases.…”
Section: Discussionmentioning
confidence: 99%